Fluorescence imaging for the anterior segment of the eye - Herzog, Joshua M.; Sick, Volker (Frontiers in Photonics, 2024)
Diagnostic technologies for the anterior segment of the eye, especially for hard-to-diagnose diseases such as microbial keratitis, are still lacking. Although in vivo confocal microscopy and optical coherence tomography are becoming more widely applicable to a variety of conditions, they are often prohibitively expensive, require specialized training and equipment, and are intrinsically insensitive to chemical changes. Here, ultraviolet-fluorescence imaging is proposed as a new technique to aid in investigation of the anterior segment. In this work, a novel two-color line-of-sight fluorescence imaging technique is described for imaging of the anterior segment. The technique is applied to seven ex vivo porcine eyes to illustrate the utility of the technique. The image data was used to estimate an effective fluorescence quantum yield of each eye at 370 nm. The eyes were then inoculated with bacteria to simulate microbial keratitis, a common sightthreatening infection, and the measurement was repeated. A simplified fluorescence-extinction model was developed to describe and analyze the relative intensities of the eye and biofilm fluorescence. Overall, the technique appears to have utility in clinical practice and with proper development may be suitable for detecting chemical changes in the eye, or the presence of foreign matter; however, further investigation is needed to develop the technique and analysis procedures into a quantitative diagnostic tool.